Vaccine health beliefs and educational influences among pediatric residents. Issue 6 (4th February 2019) - Arora, Gitanjli; Lehman, Deborah; Charlu, Sandhya; Ross, Nicole; Ardy, Adriana; Gordon, Bahareh; Pannaraj, Pia S.
Abstract: Objective: A pilot study of pediatric residents to describe perceived benefits and effects of vaccines and educational influences on vaccine practice among pediatric residents. Study design: Eighty-seven residents, from two institutions in a region with relatively high vaccine hesitancy, responded to a survey conducted in 2014–2015. Results: Residents identified professional experiences with vaccine preventable diseases (VPDs) and observing pediatricians as most impactful to their vaccine beliefs. Residents who had observed pediatric faculty agreeing to alternative or delayed vaccinations were more likely to believe this to be acceptable vaccine practice (70.1% vs. 21.1%, χ 2  = 17.778, p < 0.001). Most residents (68 [79.1%]) reported feeling confident in their ability to discuss vaccines. Conclusions: Pediatricians must be equipped with accurate vaccine health beliefs to impact parental vaccine hesitancy. This study identifies important gaps in medical education, with pediatric residents reporting limitations in their professional experience with VPDs and high rates of observing alternative vaccination practice.